ADVANCED TRAINING FOR MANAGEMENT AND FACULTY STAFF OF RUSSIAN UNIVERSITIES IN CDIO STANDARDS IMPLEMENTATION - Alexander I. Chuchalin; Marina S. Tayurskaya; Mikhail G. Myagkov (Высшее образование в России)
The paper is focused on competences development for managers and faculty staff of Russian universities providing engineering programmes consistent with the bestinternational experience in modernization of engineering education. The authors describe the structure, the content and implementation technology of the faculty training programme “Applying CDIO Concept in Engineering Education” designed by Tomsk Polytechnic University and Skolkovo Institute of Science and Technology. The paper considers the first programme results and discovers challenges of implementing CDIO Concept in Russian universities.